Optimization of Information Technology Through Intelligent System Integration : Comprehensive Exploration - Yuniana Cahyaningrum (Journal of Intelligent Systems and Information Technology, 2024)
In the era of digital transformation, intelligent system integration is the main capital for optimizing the use of information technology. This article provides a comprehensive exploration to explore how intelligent system integration forms a strong foundation for changing the outlook of information technology. The main focus of this article is utilization in operational efficiency, smarter decision making, and product and service innovation. The basic concept of intelligent system integration is explained by providing an explanation of how artificial intelligence and information technology can interact synergistically. This article also discusses the role of artificial intelligence in improving the functionality of information systems and its positive impact on decision making. The benefits of intelligent system integration in increasing operational efficiency can be explained through the automation of tasks performed, increased productivity through faster data processing, and reduced human errors. This article also shows how intelligent system integration supports better decision making through in-depth and accurate data analysis. Additionally, this article discusses how intelligent system integration drives innovation in products and services. As input for future development, this article provides an in-depth overview of intelligent system integration trends that contribute to the optimization of information technology, by opening the door to an era of innovation and greater efficiency.